Utilização de PCR multiplex para o diagnóstico etiológico da mastite bovina - Marisa Araujo Silva (2008)
Efficient control for mastitis requires sensitive, fast and specific tests to identify the agents that cause the disease. Molecular tests as the PCR have been used in microbiological diagnostics. This study was used a protocol for extraction of DNA directly in samples of milk and use of a multiplex PCR (mPCR) to identify the main agents of bovine mastitis: Staphylococcus aureus, Streptococcus agalactiae, Streptococcus uberis and Streptococcus dysgalactiae and the pathogen S. aureus resistant to methicillin (MRSA). Tests have been carried out on milk artificially contaminated with bacteria known concentration. The validation of the technique, 30 samples from bulk milk tank available from the Milk Quality Lab Analysis - LabUFMG - MAPA. To carry out the PCRs were used primers that amplify the region 16S-23S ribosomal RNA of S. aureus, S. agalactiae, S. uberis and S. dysgalactiae, and for detection of MRSA, primers used to amplify the gene that Mec A. The initiators were specific, with no amplification of DNA from other bacteria of the genus Streptococcus spp. and Staphylococcus spp. commonly found in milk. The limit of detection of microorganisms involved in infections of the mammary gland is 1000 CFU / mL by mPCR, mPCR has showed as sensitivity method for the detection pathogens in bovine milk mastitis